2020
DOI: 10.1097/sga.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Physical Activity, and Mental Health in People Living With Inflammatory Bowel Disease, Fibromyalgia, and in Healthy Controls

Abstract: This study aimed to identify biopsychosocial factors associated with fatigue, physical activity, and perceived benefits of and barriers to exercise in adults with inflammatory bowel disease and to compare them with those with fibromyalgia and healthy controls. A cross-sectional online survey was conducted. Hierarchical linear regressions were used to examine correlates of fatigue and physical activity. Analysis of variance and Kruskal–Wallis tests were used to compare levels of fatigue and physical activity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As expected, patients with active disease tend to have more barriers than those in remission, but in a study including patients with active CD, infliximab administration led to a significant improvement of physical activity level at 24 weeks [33]. Psychological interventions could also help to increase physical activity levels [28].…”
Section: Perspectives Related To Physical Activity In Inflammatory Bo...mentioning
confidence: 73%
See 1 more Smart Citation
“…As expected, patients with active disease tend to have more barriers than those in remission, but in a study including patients with active CD, infliximab administration led to a significant improvement of physical activity level at 24 weeks [33]. Psychological interventions could also help to increase physical activity levels [28].…”
Section: Perspectives Related To Physical Activity In Inflammatory Bo...mentioning
confidence: 73%
“…Depressive symptoms are frequent in IBD patients with a prevalence of over 20% [27]. Olive et al [28] showed that anxiety and depression were a limitation to physical activity in adult patients with chronic disease, including IBD. Other frequent obstacles to physical activity reported by patients with IBD included fatigue, pain and faecal urgency [9].…”
Section: Challenges Related To Physical Activity In Inflammatory Bowe...mentioning
confidence: 99%
“…32 Secondly, impaired psychological well-being, including depressive symptoms, can act as a barrier to regular PA. 33 Anxiety and depression have been identified as limitations to PA in adults with IBD. 34 Additionally, common obstacles reported by patients with IBD include fatigue, pain, fecal urgency, and muscle weakness. 35,36 Our study revealed that patients with CD and UC showed similar patterns of PA, and those in remission were more likely to engage in moderate and high-level PA.…”
Section: Discussionmentioning
confidence: 99%
“…Females are 3:1 more predicted to have fibromyalgia than men. 4 According to the London Fibromyalgia Epidemiology Study, around 4.7% of people in these 5 European countries, Germany, France, Italy, Spain, and Portugal, are concerned. 5 The symptoms can vary and are similar to those of several other conditions.…”
mentioning
confidence: 99%
“…The prevalence of fibromyalgia in the global population is 2.7%. Females are 3:1 more predicted to have fibromyalgia than men 4. According to the London Fibromyalgia Epidemiology Study, around 4.7% of people in these 5 European countries, Germany, France, Italy, Spain, and Portugal, are concerned 5…”
mentioning
confidence: 99%